An insight into the roles of ubiquitin-specific proteases in plants: development and growth, morphogenesis, and stress response - Wang, Xiuwen; Liu, Xuan; Song, Kaixuan; Du, Liang (Frontiers in Plant Science, 2024)
Ubiquitination is a highly conserved and dynamic post-translational modification in which protein substrates are modified by ubiquitin to influence their activity, localization, or stability. Deubiquitination enzymes (DUBs) counter ubiquitin signaling by removing ubiquitin from the substrates. Ubiquitin-specific Proteases (UBPs), the largest subfamily of DUBs, are conserved in plants, serving diverse functions across various cellular processes, although members within the same group often exhibit functional redundancy. Here, we briefly review recent advances in understanding the biological roles of UBPs, particularly the molecular mechanism by which UBPs regulate plant development and growth, morphogenesis, and stress response, which sheds light on the mechanistic roles of deubiquitination in plants.